(untitled) (Al-Qamar, 2022)
In the age of Jahiliyyah, the women were deprived of all their rights and were considered as a go head over heels thing in the society, but when Islam appeared, it not only gave women a high position but also gave them all the rights like men. Like a man, a woman was also given the right of ownership, the right of acquisition, economic and financial rights, and among these economic and financial rights, she gave the right of inheritance, in such a way that the share of the man was determined by making the woman’s share the basis. It is a privilege that no other religion has given except Islam. Considering Islamic teachings and Pakistani laws and constitution; we have researched the society of Bannu district (which is a Pashtun society). And came to the results that, the practical situation of our society is also sad and based on oppression. Very cruel factors and pretexts are used to deprive the women. As a Muslim nation, we have turned our backs on this precious and privileged legal right of Islam, which Allah Almighty has declared as Hududullah.